Effectiveness of Using Vlogs as Learning Media in Improving the Speaking Ability of Class X Students - Tarmusi, Riska Anisa; Maghfiroh, Ana; Indriastuti, Niken Reti; Mustikawati, Diyah Atiek; Asiyah, Siti (Jurnal Keilmuan dan Keislaman, 2024)
The use of vlogs in speaking classrooms. This research aims to (1) describe the effectiveness of vlogs as a learning medium in student speaking achievement; and (2) determine how much influence vlogs have as a medium used in learning to enhance student speaking in the tenth grade at SMAN 1 Badegan Ponorogo. This research was experimental, with a population comprising all tenth-grade students of SMAN 1 Badegan Ponorogo, consisting of ten classes. The X5 and X1 classes were randomly chosen as the sample. The data collection technique used was a post-test only. The data analysis employed was an independent samples t-test, while Cohen’s d-effect size was used to analyze the influence of vlogs as a medium in learning speaking. The results showed that for the independent samples t-test, the value (sig. 2-tailed) was 0.00, which is smaller than 0.05. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. For Cohen’s d-effect size, the value was d = 1.218. These results indicate that the use of vlogs is effective in improving the speaking achievement of tenth-grade students at SMAN 1 Badegan.